2005
DOI: 10.1103/physrevb.72.085211
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between nucleation of pentacene monolayer islands on polymeric and inorganic substrates

Abstract: We present a comparative study of the nucleation and growth of pentacene monolayer islands in the submonolayer regime onto inorganic substrates of SiO 2 and sapphire ͑Al 2 O 3 ͒ and organic substrates of poly͑methyl-metacrylate͒ ͑PMMA͒. We have determined the scaling laws that govern the saturated nucleation density per unit area N as a function of two essential deposition parameters: the deposition rate and the substrate temperature T s . For all substrates, we found N ϰ ␦ , with 0.8ഛ ␦ ഛ 1.2, and the T s dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
92
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 20 publications
11
92
2
Order By: Relevance
“…Performance has been improved by refining the film growth process [10][11][12][13] and modifying the surface of suitable gate dielectrics [2][3][4]9]. Although high performance has been achieved, the characterization and control of the threshold field and the field-effect mobility have been complicated by competing physical phenomena occurring at the oxide surface.…”
mentioning
confidence: 99%
“…Performance has been improved by refining the film growth process [10][11][12][13] and modifying the surface of suitable gate dielectrics [2][3][4]9]. Although high performance has been achieved, the characterization and control of the threshold field and the field-effect mobility have been complicated by competing physical phenomena occurring at the oxide surface.…”
mentioning
confidence: 99%
“…If the smallest stable nucleus were a dimer, E i à ¼2 $ 1.5 6 0.5 eV, in contrast with the calculated value of 0.67 eV. 35 If we instead assume that the smallest stable nucleus is a trimer, E i à ¼ E 2 þ E 3 $ 1.5 6 0.6 eV. This seems reasonable and a similar trend in formation energies was reported for the benzene molecule, which comes from the same family to that of pentacene.…”
mentioning
confidence: 47%
“…40 C, in the latter because desorption started to play a significant role. From the Arrhenius plot in Figure 4(a), we extracted E N ¼ 0.65 6 0.05 eV for 40 T 60 C. This energy scale is confirmed by ultra-violet photoemission spectroscopy measurements of a 0.4 eV energy dipole between pentacene and LSMO, 27 which is low if compared to the 1 eV found for pentacene deposited on Co. 33,34 The E N value for pentacene on LSMO can be compared with the nucleation energy found for pentacene grown on SiO 2 over the same temperature range: E N ¼ 0.78 6 0.05 eV was found for a growth rate of 0.007 nm/s, 35 which is similar to the one used in the present experiment. At higher growth rates (0.03 nm/s) P i à m¼2 E m þ i à E D ¼ 1.13 6 0.04 eV and i* ¼ 3 were reported, 36 hence E N ¼ 0.23 6 0.01 eV.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years, several studies based on OMBD grown pentacene layers have demonstrated that the pentacene grain size can be modulated via changing the deposition rate, the substrate temperature or modifying the substrate surface with organic self assembled layers [13][14][15][16][17]. However, for SuMBD grown pentacene thin films, it is more straightforward to change the grain size by tuning the pentacene kinetic energy (E k ) within the molecular beam.…”
Section: Introductionmentioning
confidence: 99%